The Application of Storytelling Therapy in Reducing Anxiety in Preschool-Aged Children Experienced Hospitalization: Literature Review - Musviro; Sri Wahyuningsih; Rella Desinta K. A. (KHD Production, 2023)
Introduction: Hospitalization is a condition that requires children to be hospitalized, this situation can cause children to feel anxious, anxiety due to hospitalization in pre-school aged children can cause excessive fear which causes children to be uncooperative, decreased appetite and decreased sleep quality so that the process of healing becomes obstructed and affects the child's growth and development if not treated immediately. Purpose: dig deeper into the effect of story telling therapy in reducing anxiety in pre-school aged children who experience hospitalization. Method: the method used in preparing the Literature review uses the PRISMA checklist and PICOS. The secondary data obtained comes from journals with predetermined discussions. Based on the results of a literature search through six databases. Researchers get 342 articles that match the keywords. The researcher then screened based on the title (n= 119), abstract (n= 59) and full text (n= 17) adjusted for inclusion criteria. Result : story telling therapy by means of storytelling which is carried out for three days starting on the first day the child enters the children's room, carried out for 10-20 minutes independently with the assistance of parents. Conclusion: Story telling therapy by telling stories can reduce anxiety, which has an influence on overcoming anxiety caused by hospitalization in preschool-aged children by controlling children's negative thoughts through stories and changing their negative outlook to a positive one through the stories told.